Extraction of trace elements by ultrasound-assisted emulsification from edible oils producing detergentless microemulsions. (1st December 2015) - Kara, Derya; Fisher, Andrew; Hill, Steve
Highlights: New ultrasound-assisted extraction method is proposed producing micro-emulsions. The method has been developed for extraction of trace elements from edible oils. This method is simple, rapid, sensitive, and cheap. It does not contain any toxic chemicals, detergents or concentrated acids. The oil-containing standards are not needed to prepare calibrations graph. Abstract: The aim of this study is to develop a new method for the extraction and preconcentration of trace elements from edible oils via an ultrasound-assisted extraction using ethylenediaminetetraacetic acid (EDTA) producing detergentless microemulsions. These were then analyzed using ICP-MS against matrix matched standards. Optimum experimental conditions were determined and the applicability of the proposed ultrasound-assisted extraction method was investigated. Under the optimal conditions, the detection limits (μg kg −1 ) were 2.47, 2.81, 0.013, 0.037, 1.37, 0.050, 0.049, 0.47, 0.032 and 0.087 for Al, Ca, Cd, Cu, Mg, Mn, Ni, Ti, V and Zn respectively for edible oils (3Sb/m). The accuracy of the developed method was checked by analyzing certified reference material. The proposed method was applied to different edible oils such as sunflower seed oil, rapeseed oil, olive oil and cod liver oil.